Evidence for a biological control on emissions of marine ice nucleating particles: laboratory, field and modeling results - McCluskey, Christina Song, author; Kreidenweis, Sonia M., advisor; DeMott, Paul J., advisor; Collett, Jeffrey L., committee member; Pierce, Jeffrey R., committee member; Mykles, Donald L., committee member (Colorado State University. Libraries, 2017)
To view the abstract, please see the full text of the document.
Keywords: ice nucleation; marine organic aerosol; ice nucleating particles; sea spray aerosol; marine aerosol